Prevention of bacterial translocation using beta-(1-3)-D-glucan in small bowel ischemia and reperfusion in rats - Araújo-Filho,Irami (2006)
PURPOSE: To investigate the role of beta-(1-3)-D-glucan on 99mTc labelled Escherichia coli translocation and cytokines secretion in rats submitted to small bowel ischemia/reperfusion injury. METHODS: Five groups (n=10 each) of Wistar rats were subjected to control(C), sham(S), group IR subjected to 45 min of bowel ischemia/60 min of reperfusion(I/R), and group I/R+glucan subjected to 45 min of bowel ischemia/60 min of reperfusion(I/R) and injected with 2mg/Kg intramuscular. Translocation of labelled bacteria to mesenteric lymph nodes, liver, spleen, lung and serum was determined using radioactivity/count and colony forming units/g(CFU/g). Serum TNFalpha, IL-1beta, IL-6, IL-10 were measured by ELISA. RESULTS: CFU/g and radioactivity/count were higher in I/R than in I/R+glucan rats. In C, S and S+glucan groups, bacteria and radioactivity/count were rarely detected. The I/R+glucan rats had enhancement of IL-10 and suppressed production of serum TNFalpha, IL-1beta and, IL-6, compared to I/R untreated animals. CONCLUSION: The beta-(1-3)-D-glucan modulated the production of pro-inflammatory and anti-inflammatory cytokines during bowel ischemia/reperfusion, and attenuated translocation of labelled bacteria.